2013
DOI: 10.1007/s10900-013-9740-7
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Knowledge, Attitude and Screening Behaviors Among Hispanics in South Texas Colonias

Abstract: This study examines breast cancer knowledge, attitudes and screening behaviors of Hispanic women living in the South Texas colonias of Maverick and Val Verde Counties. We used the Health Belief Model to analyze the effects of HBM constructs on clinical breast exam (CBE) and mammogram screening. Using a multistage systematic sampling approach we interviewed women living within these colonias. Logistic regression analysis was used to predict CBE and mammography screening behaviors. The results indicate that know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…In addition, the theory of Health Belief Model (HBM) maintained that knowledge of disease had impacts on individual's health behaviors, such as compliance to preventative services and health care suggestions. Studies performing clinical breast examination (CBE) and mammogram screening showed that the more knowledge of breast cancer and more sources of health information women had, the more likely they would participate in screening .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the theory of Health Belief Model (HBM) maintained that knowledge of disease had impacts on individual's health behaviors, such as compliance to preventative services and health care suggestions. Studies performing clinical breast examination (CBE) and mammogram screening showed that the more knowledge of breast cancer and more sources of health information women had, the more likely they would participate in screening .…”
Section: Discussionmentioning
confidence: 99%
“…Previous models have suggested a complex interplay of perceptions and social factors for health behaviors [9,37,38]. Nonetheless the majority of work has been limited to examination of independent effects [10,45-47]. This study hypothesized and found evidence to suggest women's perceptions about breast cancer moderate the association of social interactions.…”
Section: Discussionmentioning
confidence: 84%
“…First, the differential and cumulative effects of recommendations on mammography intentions among a sample of Latinas were examined. Such assessment is warranted, given the increasing evidence that recommendations are important enabling factors but are generally examined independently [10,16-19,21,28-30]. This work illuminates how providers might be particularly effective in promoting mammography use among Latinas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations